The crystal structure of the killer fibre erionite from Tuzköy (Cappadocia, Turkey) - Carlotta Giacobbe; Anna Moliterni; Dario Di Giuseppe; Daniele Malferrari; Jonathan P. Wright; Michele Mattioli; Simona Raneri; Cinzia Giannini; Laura Fornasini; Enrico Mugnaioli; Paolo Ballirano; Alessandro F. Gualtieri (IUCrJ, 2023)
Erionite is a non-asbestos fibrous zeolite classified by the International Agency for Research on Cancer (IARC) as a Group 1 carcinogen and is considered today similar to or even more carcinogenic than the six regulated asbestos minerals. Exposure to fibrous erionite has been unequivocally linked to cases of malignant mesothelioma (MM) and this killer fibre is assumed to be directly responsible for more than 50% of all deaths in the population of the villages of Karain and Tuzköy in central Anatolia (Turkey). Erionite usually occurs in bundles of thin fibres and very rarely as single acicular or needle-like fibres. For this reason, a crystal structure of this fibre has not been attempted to date although an accurate characterization of its crystal structure is of paramount importance for our understanding of the toxicity and carcinogenicity. In this work, we report on a combined approach of microscopic (SEM, TEM, electron diffraction), spectroscopic (micro-Raman) and chemical techniques with synchrotron nano-single-crystal diffraction that allowed us to obtain the first reliable ab initio crystal structure of this killer zeolite. The refined structure showed regular T—O distances (in the range 1.61–1.65 Å) and extra-framework content in line with the chemical formula (K2.63Ca1.57Mg0.76Na0.13Ba0.01)[Si28.62Al7.35]O72·28.3H2O. The synchrotron nano-diffraction data combined with three-dimensional electron diffraction (3DED) allowed us to unequivocally rule out the presence of offretite. These results are of paramount importance for understanding the mechanisms by which erionite induces toxic damage and for confirming the physical similarities with asbestos fibres.